KAJIAN PERENCANAN DINDING PENAHAN TANAH PADA KEGIATAN PEMBAGUNAN TURAP JALAN POROS TENGGARONG KABUPATEN KUTAI KARTA NEGARA - ZHAHIR SAPUTRA, US AL- (KURVA S JURNAL MAHASISWA, 2016)
Us Al-Zhahir. Saputra,Retaining wall structure calculations on the construction of an avalanche on the road KM-12 TENGGARONG KABUPATEN KUTAI KARTA NEGARA, the method of retaining walls (Dinding penahan tanah).       Roads is the so-called inter-city, the area around this road has undulating topography in terms of hilly and valley, Because it is in this area a lot of landslides. Prevention of landslides on roads Tenggarong Kabupaten Kutai Karta Negara make the construction of retaining walls (Dinding penahan tanah), The construction planning through stages such as, the actual field data collection (topography and soil investigation data) to the analysis of the shape, dimensions and stability of the construction. This construction that will hold soil landslides.        So that insecurity, especially in the avalanche area roads TENGGARONG KABUPATEN KUTAI KARTA NEGARA can be solved with the handling of avalanche using Soil Retaining Walls Structures, expected handling of avalanches by using this method can overcome the problem of landslide-avalanche in other areas not just in road course, but in other areas in Indonesia, especially in East Kalimantan.         Observations in the field show that knowledge in college many equipped with the knowledge and insight in the field,